Neuropharmacological and biological activities of Fumaria indica - Mansoor Ahmad; Meh jabeen; S. Mahboob Alam; Noor Jahan; Farah saeed; Zahid Khan (International Journal of Phytomedicine, 2015)
Crude extract of Fumaria indica was assessed for neuro-pharmacological, analgesic antimicrobial and cytotoxic activities. It decreases muscle tone as indicated by swimming induced depression test (2.41/6 min, 2.56/6 min; at the dose of 500 and 300 mg/kg respectively), it also produces dose dependant (200, 300, 500 mg/kg) increase in traction time and reduces exploratory behaviour therefore, has significant muscle relaxant and anxiolytic effect (p≤0.05) as compared to standard drugs diazepam and imipramine. The results of analgesic activity (writhing and hot plate test) were highly significant as the mean number of writhes for drug treated animals was reduced (62.7% at 500 mg/kg) as compared to the control group and reference drug aspirin. The present study also revealed that the extract of F. indica has potential to inhibit the growth against different pathogenic bacteria and fungi in vivo. Over all the F. indica has significant CNS depressant action with moderate analgesic and antifungal effects.